2008
DOI: 10.1371/journal.pone.0002421
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroup D4a Is a Marker for Extreme Longevity in Japan

Abstract: We report results from the analysis of complete mitochondrial DNA (mtDNA) sequences from 112 Japanese semi-supercentenarians (aged above 105 years) combined with previously published data from 96 patients in each of three non-disease phenotypes: centenarians (99–105 years of age), healthy non-obese males, obese young males and four disease phenotypes, diabetics with and without angiopathy, and Alzheimer's and Parkinson's disease patients. We analyze the correlation between mitochondrial polymorphisms and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 27 publications
2
81
2
Order By: Relevance
“…reporting no association between mtDNA haplogroups and EL (Pinos et al ., 2012) but Dominguez‐Garrido and co‐workers finding that the Caucasian haplogroup J (which would be associated with lower mtDNA damage) might confer a higher chance to attain high longevity (85+years) compared with other haplogroups in Northern Spaniards (Domínguez‐Garrido et al ., 2009). On the other hand, although mtDNA haplogroups D4b2b, D4a, and D5 are not associated with type 2 diabetes (Fuku et al ., 2007), they are linked with EL in Japanese population (Alexe et al ., 2007; Bilal et al ., 2008). We also showed that the mtDNA m.1382A>C polymorphism, which is specific for the ancestor haplogroup D4b2, is associated with EL in the Japanese population (Alexe et al ., 2007).…”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%
“…reporting no association between mtDNA haplogroups and EL (Pinos et al ., 2012) but Dominguez‐Garrido and co‐workers finding that the Caucasian haplogroup J (which would be associated with lower mtDNA damage) might confer a higher chance to attain high longevity (85+years) compared with other haplogroups in Northern Spaniards (Domínguez‐Garrido et al ., 2009). On the other hand, although mtDNA haplogroups D4b2b, D4a, and D5 are not associated with type 2 diabetes (Fuku et al ., 2007), they are linked with EL in Japanese population (Alexe et al ., 2007; Bilal et al ., 2008). We also showed that the mtDNA m.1382A>C polymorphism, which is specific for the ancestor haplogroup D4b2, is associated with EL in the Japanese population (Alexe et al ., 2007).…”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%
“…We previously showed that haplogroup D4a is a marker of extreme longevity in Japan 9,10) . The present study, however, produced an apparently opposite result, with haplogroup D4a appearing to be a risk factor for myocardial infarction in men.…”
Section: Haplogroup D4amentioning
confidence: 99%
“…We previously reported significant associations between specific mitochondrial haplogroups and cardiovascular and metabolic diseases as well as longevity among the Japanese 9,10) : haplogroup A was a risk factor for atherothrombotic cerebral infarction 7)…”
Section: Haplogroup Amentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many earlier reports of a relation between haplogroup and physiological function. Examples include haplogroup J in Europe, which is associated with small maximum oxygen consumption (Marcuello et al, 2009), and haplogroup D in Japan, which tends to be associated with longevity (Tanaka et al, 1998;Bilal et al, 2008). Another example is that there are differences between groups in terms of the risk of acquiring diabetes mellitus or lifestyle-related diseases Tanaka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%